Trajectories and keyframes for kinesthetic teaching: a human-robot interaction perspective - Akgun, Baris; Cakmak, Maya; Yoo, Jae Wook; Thomaz, Andrea Lockerd (2012 7th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2012)
Kinesthetic teaching is an approach to providing demonstrations to a robot in Learning from Demonstration whereby a human physically guides a robot to perform a skill. In the common usage of kinesthetic teaching, the robot's trajectory during a demonstration is recorded from start to end. In this paper we consider an alternative, keyframe demonstrations, in which the human provides a sparse set of consecutive keyframes that can be connected to perform the skill. We present a user-study (n=34) comparing the two approaches and highlighting their complementary nature. The study also tests and shows the potential benefits of iterative and adaptive versions of keyframe demonstrations. Finally, we introduce a hybrid method that combines trajectories and keyframes in a single demonstration.